2006
DOI: 10.1007/s10157-006-0405-z
|View full text |Cite|
|
Sign up to set email alerts
|

Tubulointerstitial immune complex nephritis in a patient with systemic lupus erythematosus: role of peritubular capillaritis with immune complex deposits in the pathogenesis of the tubulointerstitial nephritis

Abstract: Class IV-G (A/C) diffuse lupus nephritis and tubulointerstitial (TI) nephritis in a 31-year old woman was studied by light, immunofluorescence (IF), and electron microscopy (EM), to determine the pathogenesis of the TI lesions. The light microscopic findings showed peritubular capillaritis in the interstitium, with ruptures in the capillary structure, lysis of the surrounding tubular basement membrane (TBM), extravasated red blood cells (RBCs), the infiltration of neutrophils and mononuclear cells, and edema. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Complement activation is, however, not always beneficial in SLE. IC-mediated complement activation is thought to be an important 2704 LOOD ET AL part of SLE pathogenesis, and complement activation has been implicated in the development of nephritis in animal models as well as in humans (35,47). EndoS has been demonstrated to inhibit complement activation (36), and we verified these results by showing that IgG molecules have a markedly decreased ability to support classical pathway activation after EndoS treatment.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Complement activation is, however, not always beneficial in SLE. IC-mediated complement activation is thought to be an important 2704 LOOD ET AL part of SLE pathogenesis, and complement activation has been implicated in the development of nephritis in animal models as well as in humans (35,47). EndoS has been demonstrated to inhibit complement activation (36), and we verified these results by showing that IgG molecules have a markedly decreased ability to support classical pathway activation after EndoS treatment.…”
Section: Discussionsupporting
confidence: 67%
“…EndoS has been demonstrated to inhibit complement activation (36), and we verified these results by showing that IgG molecules have a markedly decreased ability to support classical pathway activation after EndoS treatment. Furthermore, using a functional chemotaxis assay, we showed that the decreased ability to activate the complement system led to an inhibited recruitment of PMNs, which are important cells in the pathogenesis of nephritis (35,47). Thus, treatment with EndoS could inhibit the classical pathway of complement activation and the recruitment of PMNs, two important events not only in the development of lupus nephritis, but also in local tissue inflammation in general.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, linear staining of the TBM for IgG occasionally can be seen mostly in patients taking rifampicin, methicillin, phenytoin, or allopurinol [4][5][6][7][8]. This linear pattern of staining implies the presence of antibody/ies directed against basement membrane antigens or against drug metabolites bound to the TBM [9][10][11][12]. In the absence of GBM staining and immune-complex deposition in the GBM, a granular pattern of TBM staining or immunecomplex deposits in the TBM may indicate possible druginduced antibodies directed against basement membrane component(s) or against drug metabolites bound to the TBM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, TI nephritis associated with virus infections shows similar pathological features and the infiltration of mononuclear cells of lymphocytes, plasma cells, and histiocytes, but not neutrophils [19]. Third, autoimmune TI nephritis, such as Sjögren syndrome, systemic lupus erythematosus (SLE), tubulointerstitial nephritis-uveitis syndrome, rheumatoid arthritis with arteritis (RAA), and essential cryoglobulinemia should also be considered [20][21][22]. These types of autoimmune TI nephritis are reported to have the infiltration of mononuclear cells, but not neutrophils, in the interstitium (Sjögren syndrome) or depositions of immunoglobulins and complements on the capillary walls as well as the TBM (essential cryoglobulinemia, SLE, etc.…”
Section: Discussionmentioning
confidence: 99%